Pengaruh Karakteristik Kerja Dan Persepsi Dukungan Organisasi Terhadap Produktivitas Kerja Karyawan (Studi SDM Pada Karyawan PT. Abacus Cash Solution Cabang Sukabumi) - Putri Alisa Puspita Dewi; Faizal Mulia Z; Kokom Komariah (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Based on the results of the questionnaire, it was found that problems in work productivity experienced a decline, this could be due to a lack of relationship between employees and superiors or a lack of improving relations so that it could result in a lack of work productivity for employees, and also their work characteristics. This research was carried out in order to aim to describe the characteristics of work, perceptions of organizational support, and also employee productivity at PT ABACUS Cash Solution Sukabumi employees. The reason for this research is that there are problems with work productivity. The object of this research is work characteristics, perceived organizational support and employee productivity. The research method used in this research is the associative and descriptive method with a quantitative approach. The population in this study were employees with a total of 153 employees using saturated sampling. The type of data used is primary and secondary data, and the measurement technique uses a semantic difference scale. The data analysis techniques used in this research are validity test, reliability test, multiple linear regression test, determination test and research model testing (F test) and also hypothesis testing (T test). The results of this study can show that the variables of work characteristics, perceptions of organizational support and employee work productivity have a strong correlation between work characteristics, perceptions of organizational support with a score of 0.769 and also the magnitude of the influence of work characteristics and perceptions of organizational support on work productivity of 59.1 % and the remaining 40.9% is influenced by other factors outside the study.